The Effect Of Zakat Performing Ratio On Financial Performance Of Sharia Commercial Banks Moderated By Sharia Banking Company Size (Study on Islamic Commercial Banks 2016-2020 Period) - Bakti Prayogo; Fetria Eka Yudiana (Bursa : Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of the Shariah Compliance (Islamic Income Ratio, Profit Sharing Ratio, Zakat Performance Ratio) and Islamic Social Reporting on Financial Performance with Company Size as a Moderation Variabel in Islamic Commercial Banks for the 2016-2020 period. This type of research is a quantitative research using secondary data in the form of panel data and using Moderated Regression Analysis as data analysis. The data that has been obtained is then processed using the E-views 9 application tool. Based on the results of this study shows that the Islamic Income Ratio (IsIR) variable has a positive and insignificant effect on Financial Performance, Profit Sharing Ratio (PSR) has a positive and insignificant effect on Financial Performance, Zakat Performance Ratio (ZPR) has a positive and significant effect on Financial Performance, Islamic Social Reporting (ISR) has a negative and insignificant on Financial Performance, and Company Size has a positive and insignificant on Financial Performance. Company Size can moderate the effect of Zakat Performance Ratio (ZPR) but is unable to moderate the effect of Islamic Income Ratio (IsIR), Profit Sharing Ratio (PSR), and Islamic Social Reporting (ISR) on Financial Performance